KARAKTERISASI BIOKIMIAWI RIZOBAKTERI ASAL GULMA BERDAUN LEBAR YANG BERPOTENSI SEBAGAI DELETERIOUS RHIZOBACTERIA - Asniah, Asniah; Rakian, Tresjia C.; Wangadi, Sri; Gusnawaty, HS (Jurnal Agroteknos, 2013)
The research aimed to know biochemical characters of rhizobacteria from broadleaf weed that are potential as deleterious rhizobacteria. The research was conducted at Agronomy Laboratory of Agriculture Faculty Halu Oleo University Kendari from January until March 2013. The results showed that 9 of 10 rhizobacteria isolates tested from broadleaf weeds rhizosphere had the ability to solubilize phosphate with different diameters. For nitrogen fixation ability, all isolates tested were potential but only isolates of ML-01 and KL-06 had high capability. All isolates had different ability to produce IAA, with isolates of KL-06 produced higher concentration of IAA (33,07 ppm) compared to other isolates. Isolates that had the ability to produce HCN were isolates BL-07, with filter paper change from yellow to dark brown, and BL-08 and BL-03 light brown color changes indicated to that the production of HCN was increased. Result of research showed that some isolates tested had biochemical character as deleterious rhizobacteria by the ability to solubilize phosphate, fix nitrogen, produce IAA and HCN. Keywords: biochemical characterization, rhizobacteria, broadleaf weeds, deleterious.